The Effect of Prenatal Massage Therapy on Pregnant Women in the Third Trimester on Back Pain Complaints at Primary Health Care Bulango - Karmila Daud; Widia Shofa Ilmiah; Anik Sri Purwanti (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2025)
Back pain is one of the most common complaints experienced by pregnant women, especially during the third trimester of pregnancy. This discomfort is generally caused by physiological and biomechanical changes in the body, such as an increase in body weight, a shift in the center of gravity, and hormonal changes that affect muscle and joint flexibility. If not managed properly, back pain can reduce mobility, interfere with daily activities, and impact the quality of life of pregnant women. One safe and non-pharmacological method to reduce back pain is prenatal massage therapy. This study aimed to determine the effect of prenatal massage on reducing back pain among pregnant women in the third trimester at Primary Health Care (PHC) Bulango. This research used a pre-experimental design with a one-group pretest–posttest approach. The sample consisted of 30 pregnant women in their third trimester who were selected through purposive sampling. Data collection was carried out using observation and interviews with a numerical pain rating scale administered before and after the prenatal massage intervention. The massage sessions were performed following standardized prenatal massage procedures focusing on the lower back area. Data were analyzed using the paired t-test with the assistance of SPSS software. The results showed a statistically significant difference in back pain scores before and after the intervention, with a p-value of 0.000 (p < 0.05). This finding indicates that prenatal massage effectively reduces back pain in third-trimester pregnant women. Based on these results, prenatal massage can be recommended as a safe, non-invasive, and beneficial complementary therapy to improve maternal comfort during pregnancy. Incorporating prenatal massage into routine antenatal care could enhance the overall well-being and quality of life of expectant mothers.